Batasan Perbuatan Hukum Orang Dewasa Yang Berada Dalam Pengampuan - Cakra Manggala Ganda; Miftakhul Huda (UNES Law Review, 2024)
Adulthood is a phase of life that occurs after entering the adolescent life stage, When someone is in the adult life phase to the elderly, some people can experience a decrease in organ function, with the loss of organ function can result in loss of memory to skills. Skills are very useful for survival, can make a person strong and resilient in living personal and social life. In Indonesia, skills and authority to act are regulated in article 330 and article 1331 BW. Acting is also included in skills and is a general authority to take legal action and skills to act also generally and in principle apply to everyone, in Indonesia skills are included in the category of guardianship.